Do MRI and ultrasound of the anterior pelvis correlate with, or predict, young football players' clinical findings? A 4-year prospective study of elite academy soccer players. Issue 3 (6th March 2014) - Robinson, Philip; Grainger, Andrew J; Hensor, Elizabeth M A; Batt, Mark E; O'Connor, Philip J
Abstract : Aims: To prospectively follow a cohort of elite young male professional soccer players with sequential symptom questionnaires and imaging of the anterior pelvis to determine the prevalence and severity of imaging findings. Methods: 34 male athletes (mean age 16.5 years) underwent clinical examination, history/symptom questionnaire, ultrasound and 1.5 T MRI of the anterior pelvis. Athletes then underwent annual questionnaire and ultrasound with MRI also performed every 18 months. Two experienced radiologists scored ultrasound (consensus) and MRI (independently) for abnormality including pubic bone, capsule and tendon oedema and scores correlated with symptoms and presence or absence of previous injuries. Results: Over 4 years the participants fell from 34 to 22 in number with no withdrawals due to groin injury. On study entry no athletes had undergone previous hip or pelvic surgery. On MRI pubic bone oedema, secondary cleft, capsule/tendon oedema and enhancement did not differ substantively between players with and without history of previous injury. κ Analysis for MRI scoring showed excellent agreement (0.84–0.96) for pubic bone marrow oedema, secondary cleft, capsule/tendon oedema and enhancement. On ultrasound inguinal wall motion and adductor tendinopathy did not differ substantively between players with and without history of previous injury. Stability of imaging assessments over time showed no consistent difference. Conclusions: Pubic bone marrow and parasymphyseal findings (cleft, capsule/tendon oedema) on MRI or inguinal canal ballooning on ultrasound were frequently found in asymptomatic athletes and did not predict injury or symptom development.